Validation of risk perception questionnaire for covid-19: Indonesian version for critical care nurses - Diki Ardiansyah; Diah Tika Anggraeni (Alma Ata University Press, 2022)
Background : The high need for intensive care in COVID-19 patients often has an impact on large workloads, long-term fatigue, and exposure to infections. Perception plays an important role in the desire to change behavior, including the impact. However, to date, there is no valid and reliable assessment instrument to measure risk perceptions of Covid-19. Objectives: This study aims to examine the validity and reliability of the nurse's risk perception questionnaire in the care of Covid-19 patients in the Intensive Care unit according to the situation in Indonesia.Methods: This study was conducted on nurses who treat COVID-19 patients in the ICU. The research design was carried out in a cross-sectional manner. The sampling technique used was total sampling, with a total of 35 respondents. The researcher conducted an analysis through five stages, namely translation and cross-cultural adaptation of the instrument in order to obtain the Indonesian version of the Risk Perception questionnaire. After that, a retrial was carried out on 15 nurses who worked in the COVID-19 room. The statistical test was used to test the validity and reliability using Cronbach's alpha and reliability analysis.Results: The results of the validity test with Cronbach's alpha of 0.379 - 0.766 with a reliability test using analytical reliability of 0.943. The value of the r table is 0.3338. There are 5 items from the risk perception questionnaire that are not valid after the construct validity test. The researcher then issued 5 invalid items. So that there are 42 out of 47 questionnaire items that are relevant to the condition of nurses caring for COVID-19 patients in the ICU in Indonesia.Conclusions: This risk perception questionnaire is valid and reliable, so the risk perception questionnaire can be used in Indonesia to evaluate nurses' risk perceptions in treating COVID-19 patients in the ICU. Researchers recommend health care providers evaluate nurses' risk perceptions using this questionnaire.